2014
DOI: 10.1017/s0144686x14000300
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational proximity and the residential relocation of older people to care institutions and elsewhere

Abstract: We investigated the extent to which the geographic proximity of adult children affected the relocations of older people in the Netherlands in 2008. A major contribution of this study is the examination of the differentiation between relocation to care institutions and elsewhere. Data from the Dutch population register linked to complementary datasets were analysed for nearly one million inhabitants aged 75 and above, using multinomial logistic regression models to estimate the effects of intergenerational prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 79 publications
(124 reference statements)
4
36
0
Order By: Relevance
“…Informal support and family contact play a crucial role in this. Earlier research suggests that the proximity of children postpones moves to residential care institutions (Van der Pers et al, ). A major contribution of this study is to scrutinise whether and how interfamily mobility plays its part in children's support provision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informal support and family contact play a crucial role in this. Earlier research suggests that the proximity of children postpones moves to residential care institutions (Van der Pers et al, ). A major contribution of this study is to scrutinise whether and how interfamily mobility plays its part in children's support provision.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have identified geographic distance between parents and their adult children as an important determinant of intergenerational support. A closer proximity facilitates contact between family members, increases the possibility to exchange certain types of support and postpones older people's moves to residential care institutions (Bonsang, ; De Jong Gierveld & Fokkema, ; Grundy & Shelton, ; Haberkern & Szydlik, ; Joseph & Hallman, ; Knijn & Liefbroer, ; Mulder & Van der Meer, ; Van der Pers, Kibele, & Mulder, ). Parent–child proximity is generally established during children's early adult life (Kolk, ).…”
Section: Introductionmentioning
confidence: 99%
“…While there can be advantages to relocating to aged care accommodation especially in situations of deteriorating physical or cognitive health, research shows that quality of life is sometimes better when older people stay at home (Sixsmith et al, 2014). Some studies show that relocation to care accommodation can be associated with stress (Van der Pers, Kibele, & Mulder, 2015), loss of independence (Björk et al, 2016) and accelerated cognitive and physical decline (Harmand et al, 2014) while continued independence can enable older people to maintain wellbeing even in the face of illness and disability (Zeitler & Buys, 2015). On the other hand, living at home can assist older people to retain autonomy and control over the details of daily living (Van Dijk, Cramm, Van Exel, & Nieboer, 2015).…”
mentioning
confidence: 99%
“…A U.S.-based study observed that among older people with ADL limitations, those who had all children living more than 30 miles were more likely to go to a nursing home than those who had a child living close by ( Deane, Spitze, Ward, & Zhuo, 2015 ). In Netherlands, a study found that older parents were more likely to move to a care facility if they had all children living more than 40 km away ( Van Der Pers, Kibele, & Mulder, 2015 ). Elders who lived alone without a child were found most likely to have adverse health outcomes in Myanmar and Vietnam ( Teerawichitchainan, Knodel, & Pothisiri, 2015 ).…”
Section: Discussionmentioning
confidence: 99%